Mean squared load criteria for scheduling independent tasks - Dzemyda, Gintautas (Zielona Góra: Uniwersytet Zielonogórski)
Results of this paper extend the set of criteria which characterize the scheduling quality as well as the set of possible scheduling strategies. A new view on the minimum makespan criterion is presented in terms of the mean squared load of processing units.
Keywords: parallel processing; scheduling; combinatorial problems; minimum makespan problem; mean squared load